Patient and family engagement strategies for children and adolescents with chronic diseases: A review of systematic reviews. Issue 9 (September 2021) - Smith, Brandon M.; Sharma, Ritu; Das, Asar; Aboumatar, Hanan; Pitts, Samantha I.; Day, Jeff; Holzhauer, Katherine; Bass, Eric; Bennett, Wendy L.
Highlights: Patient and family engagement is important for patient and family-centered care. Best practices for engagement of pediatric chronic disease are needed. Direct care strategies focus on self-management support and shared decisionmaking. Asthma is the most frequently studied condition for direct care strategies. More research on engagement is needed at the health system and community levels. Abstract: Objective: Patient and family engagement is important for family-centered care, particularly for children and adolescents with chronic disease. We aimed to 1) identify available evidence from systematic reviews on engagement strategies used to help children, adolescents, and their caregivers manage chronic conditions, and 2) identify gaps in the literature. Methods: We searched PubMed and CINAHL from January 2015 to January 2020 for systematic reviews on patient and family engagement strategies in the pediatrics population (<18 years). Strategies were categorized by direct patient care, health system, and community policy levels. We excluded reviews if interventions were unidirectional or without comparison. Results: We identified 25 systematic reviews. Twenty-two evaluated direct patient care, with 14 (279 unique studies) exclusively in pediatrics and 8 (24 unique studies) that included pediatric results with adults. Three reviews (9 unique studies) evaluated health system strategies. Direct patient care reviews focused on self-management support (n = 16) and shared decisionmaking (n = 6). Asthma was the most frequently evaluated condition (n = 14). Conclusions and practice implications: Engagement strategies for children and adolescents with chronic disease are focused on direct patient care, particularly for asthma. More research is needed to address engagement for broader populations, expanded outcomes, and at health system and community levels.